2008
DOI: 10.1039/b717928f
|View full text |Cite
|
Sign up to set email alerts
|

Selective partial hydrogenation of hydroxy aromatic derivatives with palladium nanoparticles supported on hydrophilic carbon

Abstract: Selective hydrogenation of phenol to cyclohexanol in the aqueous phase was achieved using a new catalytic system based on palladium particles supported on hydrophilic carbon prepared by one-pot hydrothermal carbonisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
147
1
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(156 citation statements)
references
References 19 publications
2
147
1
4
Order By: Relevance
“…On the basis of these results, it can be concluded that the phenol hydrogenation proceeds through the pathways illustrated in Scheme 1: phenol is sequentially hydrogenated through cyclohexanone to cyclohexanol (paths i and iii) and directly to cyclohexanol (path ii). In contrast to the present results, almost 100% selectivity to cyclohexanone was obtained with supported Pd catalysts in both the gas-phase [1][2][3][4][5][6][7][8][9][10][11][12] and liquid-phase [13][14][15][16]25] hydrogenation reactions. The direct formation of cyclohexanol from phenol (path ii) is unlikely to occur with these Pd catalysts.…”
Section: Reaction Pathways Of Phenol Hydrogenationcontrasting
confidence: 54%
See 1 more Smart Citation
“…On the basis of these results, it can be concluded that the phenol hydrogenation proceeds through the pathways illustrated in Scheme 1: phenol is sequentially hydrogenated through cyclohexanone to cyclohexanol (paths i and iii) and directly to cyclohexanol (path ii). In contrast to the present results, almost 100% selectivity to cyclohexanone was obtained with supported Pd catalysts in both the gas-phase [1][2][3][4][5][6][7][8][9][10][11][12] and liquid-phase [13][14][15][16]25] hydrogenation reactions. The direct formation of cyclohexanol from phenol (path ii) is unlikely to occur with these Pd catalysts.…”
Section: Reaction Pathways Of Phenol Hydrogenationcontrasting
confidence: 54%
“…In the cases of vapor phase hydrogenation, high temperatures are needed, which usually cause catalyst deactivation by coking during the reaction. In a few studies, liquid phase hydrogenation of phenol was carried out with Pd catalysts [13][14][15][16]. However, high reaction temperatures or long reaction time were still required to obtain high phenol conversions.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon spheres embedded with palladium nanoparticles were synthesized by HTC of furfural and palladium acetylacetonate. During the HTC process, the palladium acetylacetonate was reduced to elemental metallic palladium nanoparticles [70].…”
Section: Applications Of Hydrothermal Carbonsmentioning
confidence: 99%
“…Matos et al [14] reported that the phenol hydrogenation produces cyclohexanone over a polar TiO 2 -C-supported Pd catalyst, while it produces cyclohexanol over a hydrophobic TiO 2 -C-supported catalyst. Makowski et al [15] reported that the hydrophilic carbon-supported Pd catalyst showed very high cyclohexanone selectivity in phenol hydrogenation. These results suggest that the hydrophilicity/hydrophobicity of CNTs could affect the catalytic properties of CNTs-supported metal catalysts for phenol hydrogenation.…”
Section: Introductionmentioning
confidence: 99%